Transaction cost theory, political theory and resource dependency theory in the light of unconventional aspect - Htay, Sheila Nu Nu; Syed, Ahmed Salman (International Organisation of Scientific Research (IOSR), 2013)
Islam as a comprehensive religion, it molds our way of life comprehensively from the religious activities to the business activities. Muslims are required to abide the Islamic teachings in their private lives as well as dealing with public. When the business dealings are examined, the top corporate players monitor the management of the company and these players are in turn observed the best corporate governance practices and guidelines issued by the respective regulators. From the conventional perspective, these guidelines are developed based on the theories developed by the prior researchers using their rational thinking and learning from the past experiences. In Islam, it is believed that human being has limited knowledge and thus, their theories founded on rational thinking might not be comprehensive and valid unless it combines with the revealed knowledge. Thus, the purpose of this paper is to examine whether the prevailing corporate governance theories such as transaction cost theory, political theory and resource dependency theory are in line with Shari’ah. It has been found out that none of them are completely in line with Islamic teachings. Thus, this paper suggests the regulators which allow the activities of Islamic finance should revisit their existing conventional corporate governance principles to ensure that they are in line with MaqasidShari’ah and applicable to the needs of the Islamic finance industry.